KPT Top Management Revitalisation Programme 2026 strengthens strategic leadership through reform mindset - Mohd Mukhris, Awang (UMPSA, 2026)
KUALA TAHAN, 12 April 2026 – The Ministry of Higher Education (MOHE), in strategic collaboration with Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), successfully organised the 2026 MOHE Top Management Revitalisation Programme, themed ‘Mind Revitalisation, Action Reform’.